2010
DOI: 10.1016/j.apenergy.2010.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of multi-deck medium temperature display cabinets with the integration of CFD and cooling coil models

Abstract: In this paper, the model for the multi-deck medium temperature display cabinets is developed with the integration of CFD and cooling coil sub-models. The distributed method is used to develop the cooling coil model with the airside inputs from the outputs of the CFD model. Inversely, the airside outputs from the cooling coil model are used to update the boundary conditions of the CFD model. To validate this cabinet model, a multi-deck medium temperature display cabinet refrigerated with a secondary refrigerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ge and Tassou [21] developed correlations for heat transfer across air curtain with reasonable agreement with experimental data in steady-state conditions. Ge et al [22] developed an ORDC model integrating CFD and cooling coil models. The airside inputs of the cooling coil model are the outputs of the CFD model, and, inversely, the airside outputs from the cooling coil model are used to update the boundary conditions of the CFD model.…”
Section: Introductionmentioning
confidence: 99%
“…Ge and Tassou [21] developed correlations for heat transfer across air curtain with reasonable agreement with experimental data in steady-state conditions. Ge et al [22] developed an ORDC model integrating CFD and cooling coil models. The airside inputs of the cooling coil model are the outputs of the CFD model, and, inversely, the airside outputs from the cooling coil model are used to update the boundary conditions of the CFD model.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous simulation studies, the steady RANS model has been confirmed to be generally accurate to predict the natural convection [12][13][14]16].…”
Section: Methodsmentioning
confidence: 87%
“…Most of the investigations on the characteristics of the infiltration with large temperature difference are steady simulations in the research field of the refrigerated display cabinets with air curtains [13][14]. Although Foster et al [6,7] and Micheaux et al [5] investigated the infiltration with large temperature difference based on the …”
Section: Introductionmentioning
confidence: 98%
“…A validated cabinet model could be an efficient tool to examine cabinet performance, conduct optimal designs and most importantly, imitate actual cabinet operation. Accordingly, a compete cabinet model was developed by integrating two parts of cabinet sub-models in which a CFD model was utilised to predict the air flow dynamics surrounding the cabinet from the evaporator outlet to the inlet while a detailed model was developed for the evaporator [8]. Such a complete model is believed more practical since unnecessary assumptions of boundary conditions at the evaporator inlet and outlet were disregarded.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%